DIGITAL DIVIDE IN EUROPEAN UNION - STATE AND PERSPECTIVES - Đorić, Žarko (Economic Outlook, 2022)
The term digital divide (digital social inequality, also a "first world problem") refers to the gap between demographics and regions that have access to modern information and communications technology and those that don’t have access. The primary aim of the paper is to look at the very concept of the digital divide, as well as the possibility of bridging it in order to achieve the fundamental goal embodied in a more inclusive Europe, using the latest EUROSTAT data, for the years 2019 and COVID-19 2021. The paper performs a classical comparison of quantitative information of observed phenomena according to various criteria and from different time frames, specifically before the pandemic and during the pandemic. A more detailed review of the literature points to the persistence of the gap of both the first (material access), and the second (skills and uses) and the third level (outcomes of differentiated access and use) in the European Union, which is also evident in the conditions of the COVID-19 pandemic which has confirmed the need to turn to digital transformation which is accelerated and adequately managed. The digital divide is manifested between the EU Member States, with a particularly pronounced dividing line between northern and southern European countries. In order to narrow digital divide as much as possible, a strong commitment is needed, not only from policy makers at EU level, but also from Member States, primarily towards raising investment in research and innovation, the diffusion of ICT literacy and the deployment of smart technologies for society.